CONSTRUCTIVISTIC-BASED ENTREPRENEURSHIP LEARNING MODEL, ITS INFLUENCE ON THE ATTITUDES, ENTREPRENEURIAL COMPETENCE AND ENTREPRENEURIAL MOTIVATION OF STUDENTS OF BUSINESS ADMINISTRATION DEPARTMENT, STATE POLYTECHNIC OF MALANG - Fullchis Nurtjahjani; Joko Samboro (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this research is to test the suitable structural learning model and which a learning model of entrepreneurship based in constructivism can build attitude and entrepreneurial motivation of students. This research includes explanatory research or hypothesis testing. The subject of this research is from the student in Business Administration Polytechnic State of Malang who has passed the Entrepreneur subject. The sampling has been done by multistage sampling by random sampling. Data analysis used Structural Equation Modeling (SEM). Based on the results of the study and discussion, it shows that constructivist-based entrepreneurship learning has an effect on entrepreneurial attitudes and entrepreneurial competence. Furthermore, constructivist-based entrepreneurship learning has no effect on entrepreneurial motivation. Other results show that entrepreneurial attitudes and competence have no effect on entrepreneurial motivation. The indirect hypothesis shows that there is an effect of constructivist-based entrepreneurship learning on entrepreneurial attitudes but there is no significant effect on entrepreneurial motivation, and there is a significant effect between constructivist-based entrepreneurship learning) and entrepreneurial competence but there is no positive and significant effect on the entrepreneurial motivation variable.